Teladan Yeremia dalam Menjawab Panggilan Allah di Tengah Tantangan Anak Muda Masa Kini - Heppy Agustina Harefa; Peniel Telaumbanua (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2026)
This study aims to examine the example of the prophet Jeremiah in responding to God's call and its relevance for young Christians in the modern era characterized by instant culture and digital social pressures. Today's young generation often faces confusion in finding the meaning of their calling in life amidst worldly values that emphasize material success. Using a qualitative approach through a literature study method, this study interprets the text of Jeremiah 1:4-10 hermeneutic-theologically and relates it to the spiritual dynamics of young people. The results of the study indicate that God's call is divine and personal, where God calls based on His love and plan, not human ability. Jeremiah, who felt unworthy because of his youth, is an example of faith and obedience amidst limitations. This study emphasizes that responding to God's call means courageous obedience and loyalty amidst the current of pragmatic culture.